Meta-avaliação: processo de autoavaliação institucional de Universidades de Fronteira na América do Sul - Silva, Clarice de Fátima da (2020)
The present study has the goal of meta-evaluating the self-evaluation process of South American Frontier Universities. Therefore, the following problematic is considered: how does the meta-evaluation allow for improvement in the institutional self-evaluation process of South American Frontier Universities? The timeframe selected for data collection regards the final report of self-evaluation base-year 2018 from a sample of two South American Frontier Universities. For data collection, primary and secondary sources were utilized, as well as the legislation of politics for institutional evaluation. This is, therefore, a qualitative and documental research. For data collection, organization and analysis, there were content analysis based on Bardin (2011), Saldaña (2013), and other authors such as: Gil (2010), Marconi and Lakatos (2017). For the application of International Evaluation Quality Standards, the JCSEE (Joint Committee on Standards for Educational Evaluation) was considered. The software ATLAS.ti, version 8.4.24, was used to complete the analysis. The educational policy considered in this research was made by the National Higher Education Assessment System (SINAES) of Brazil for analysis of the IES reports. The results of this research point to significative change on higher education that substantiate, justify and orientate the educational politics in the institutional evaluation of the involved universities. The data and results signal that one of the institutions met mainly the criteria in the preparation and promotion steps, with its most vulnerable point in the execution step, while in the other IES, the results of the preparation, execution and promotion steps of the institutional self-evaluation process indicate that it met the quality standards of JCSEE. At last, the application of meta-evaluation in the IES allowed for indication of aspects in the improvement of the institutional self-evaluation of these South American Frontier Universities.